Editorial - Johannes A Smit; Denzil Chetty (Journal for the Study of Religion)
In this Festschrift we want to both celebrate Professor Dr. Martin Prozesky’s academic career as student and scholar in Religious Studies and Ethics, and his substantial impact on South Africans of all walks of life through his thought, publications, and practical ethics training in the academy, and in the corporate and public domains. This comes after nearly 50 years since he started teaching Comparative Religion in the then Rhodesia (now Zimbabwe) in 1969, and also 40 years, since he started as Senior Lecturer in 1977, at the then University of Natal, Pietermaritzburg campus, teaching Philosophy of Religion in the Depart-ment of Divinity1. It is also nearly 40 years since he was introduced to Process Philosophy and wrote his review of Process Theology: An Introductory Exposition, by John B. Cobb Jr. and David Ray Griffin (1979). It is also now 10 years since he took early retirement from the University of KwaZulu-Natal in 2007, and the publication of his very significant Conscience: Ethical Intelligence for Global Well-Being (2007). This year, Prof. Dr. Prozesky will celebrate his seventy-fourth birthday, and we are celebrating his contributions to our discipline, and its sub-disciplines, at the 40th Congress of the Association for the Study of Religion in Southern Africa (ASRSA).